THE ROLE OF THE COMMITTEE ON THE ELIMINATION OF DISCRIMINATION AGAINST WOMEN (CEDAW) IN PROTECTING AND ENSURING THEIR RIGHTS - Nosirova Marjona (Scholar Express Journals, 2025)
This article reveals the organization, structure, goals and tasks of the Committee on the Elimination of Discrimination against Women (CEDAW). Also, the Charter of the Committee, the provisions of the Convention on the Elimination of All Forms of Discrimination against Women are included
Keywords: UN; Committee on the Elimination of Discrimination against Women; expert